Penerapan Problem Based Learning (PBL) Melalui Media Game Lembar Pertanyaan Untuk Meningkatkan Pemahaman Maharah Kitabah Bahasa Arab Siswa Kelas XI MAN Purwakarta - Cahyainda Lailazhizah; Enan Kusnandar; Ahmad Fajar (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Arabic is an important language for Muslims, serving as the language of the Quran and other Islamic sciences. Arabic language learning in madrasas (Islamic schools) needs to be directed so that students not only memorize vocabulary and grammar but also master comprehensive language skills such as reading, speaking, listening, and writing (Maharah Kitabah). Maharah Kitabah is often challenging, especially at the Madrasah Aliyah (Islamic Senior High School) level, as it requires an understanding of grammar and grammar rules, as well as the ability to construct accurate and systematic sentences. Maharah Kitabah learning has tended to be conventional and teacher-centered, resulting in low student engagement and suboptimal outcomes. This study implemented a Problem-Based Learning (PBL) model that focuses on solving real-world problems by integrating question-based games as a medium to increase student motivation and engagement. The study used a Classroom Action Research (CAR) method with 36 11th-grade students from MAN Purwakarta as subjects. The procedure involved two learning cycles, with data collected through comprehension tests, observations, motivational questionnaires, and interviews. The results of the study showed a significant increase in students' understanding of the Maharah Kitabah, with an average pretest score of 55 increasing to 78 in the final cycle posttest